2015
DOI: 10.1080/23262133.2015.1122700
|View full text |Cite
|
Sign up to set email alerts
|

Engineered AAV vectors for improved central nervous system gene delivery

Abstract: Adeno-associated viruses (AAV) are non-pathogenic members of the Parvoviridae family that are being harnessed as delivery vehicles for both basic research and increasingly successful clinical gene therapy. To address a number of delivery shortcomings with natural AAV variants, we have developed and implemented directed evolution—a high-throughput molecular engineering approach to generate novel biomolecules with enhanced function—to create novel AAV vectors that are designed to preferentially transduce specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Complementary approaches to reducing off-target transduction aim at enhancing vector tropism for the desired organ or cell type, while (simultaneously) reducing tropism for off-target systems. De novo synthesis of novel AAV capsids, or modification of existing capsids (through directed evolution [15], mutagenesis of specific amino acids in the capsid [16], or incorporation of specific targeting peptides [17]) have all proved to improve CNS transduction, while decreasing transduction in peripheral organs. In 2016, Deverman et al [18] reported a significant advance in capsid design, when they published a selection method called Cre recombination-based AAV targeted evolution (CREATE)-which allows selection of AAV capsids that efficiently transduce defined Cre-expressing cell populations in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary approaches to reducing off-target transduction aim at enhancing vector tropism for the desired organ or cell type, while (simultaneously) reducing tropism for off-target systems. De novo synthesis of novel AAV capsids, or modification of existing capsids (through directed evolution [15], mutagenesis of specific amino acids in the capsid [16], or incorporation of specific targeting peptides [17]) have all proved to improve CNS transduction, while decreasing transduction in peripheral organs. In 2016, Deverman et al [18] reported a significant advance in capsid design, when they published a selection method called Cre recombination-based AAV targeted evolution (CREATE)-which allows selection of AAV capsids that efficiently transduce defined Cre-expressing cell populations in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…One active area of research is the development of viral vectors with more precise cell-type-targeting capabilities via the directed evolution of AAV capsids. Several groups have generated libraries of AAV capsid proteins, applied them to animal models, and examined their transduction in a cell-type-specific manner (164,165). Deverman et al used such a method to develop an intravenously injected AAV vector capable of transducing the mouse brain 40-fold better than could be achieved with standard vectors (166).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Variations on AAV serotypes occur either naturally or deliberately by introducing mutations in capsid proteins (Kotterman & Schaffer, ). Techniques such as Cre‐recombination‐based AAV targeted evolution (CREATE) help engineer capsids with desirable cell‐ or tissue‐targeting capabilities (Chan et al., ; Deverman et al., ; Kotterman & Schaffer, ; Kotterman, Vazin, & Schaffer, ).…”
Section: Viral Tropism: Serotypes and Pseudotypesmentioning
confidence: 99%